Effects of a High‐Intensity Functional Exercise Program on Dependence in Activities of Daily Living and Balance in Older Adults with Dementia. Issue 1 (19th January 2016) - Toots, Annika; Littbrand, Håkan; Lindelöf, Nina; Wiklund, Robert; Holmberg, Henrik; Nordström, Peter; Lundin‐Olsson, Lillemor; Gustafson, Yngve; Rosendahl, Erik
Abstract : Objectives: To investigate the effects of a high‐intensity functional exercise program on independence in activities of daily living (ADLs) and balance in older people with dementia and whether exercise effects differed between dementia types. Design: Cluster‐randomized controlled trial: Umeå Dementia and Exercise (UMDEX) study. Setting: Residential care facilities, Umeå, Sweden. Participants: Individuals aged 65 and older with a dementia diagnosis, a Mini‐Mental State Examination score of 10 or greater, and dependence in ADLs (N = 186). Intervention: Ninety‐three participants each were allocated to the high‐intensity functional exercise program, comprising lower limb strength and balance exercises, and 93 to a seated control activity. Measurements: Blinded assessors measured ADL independence using the Functional Independence Measure (FIM) and Barthel Index (BI) and balance using the Berg Balance Scale (BBS) at baseline and 4 (directly after intervention completion) and 7 months. Results: Linear mixed models showed no between‐group effect on ADL independence at 4 (FIM=1.3, 95% confidence interval (CI)=−1.6–4.3; BI=0.6, 95% CI=−0.2–1.4) or 7 (FIM=0.8, 95% CI=−2.2–3.8; BI=0.6, 95% CI=−0.3–1.4) months. A significant between‐group effect on balance favoring exercise was observed at 4 months (BBS=4.2, 95% CI=1.8–6.6). In interaction analyses, exercise effects differed significantly between dementia types. Positive between‐group exercise effects were found in participants with non‐Alzheimer's dementia according to the FIM at 7 months and BI and BBS at 4 and 7 months. Conclusion: In older people with mild to moderate dementia living in residential care facilities, a 4‐month high‐intensity functional exercise program appears to slow decline in ADL independence and improve balance, albeit only in participants with non‐Alzheimer's dementia.